2019
DOI: 10.2319/020219-74.1
|View full text |Cite
|
Sign up to set email alerts
|

Dental arch size and shape after maxillary expansion in bilateral complete cleft palate:A comparison of three expander designs

Abstract: Objective: The objective of this study was to compare the effects on upper dental arch size and shape after maxillary expansion with Hyrax, Quad-helix, and a differential opening expander in bilateral cleft lip and palate (BCLP) patients. Materials and Methods: Seventy-five BCLP patients were divided into three groups: Hyrax (H), Quad-helix (QH), and Expander with differential opening (EDO). Digital models were obtained befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…A previous study reported that the Hyrax expander did not produce a change in arch shape. 8 However, that study was conducted in patients with bilateral complete cleft lip and palate, which might explain the discrepancy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study reported that the Hyrax expander did not produce a change in arch shape. 8 However, that study was conducted in patients with bilateral complete cleft lip and palate, which might explain the discrepancy.…”
Section: Discussionmentioning
confidence: 93%
“…Arch size and shape were measured using the software Stratovan Checkpoint (Stratovan Corporation, Davis, Calif) and MorphoJ (Klingenberg Lab, Manchester, UK) according to a previous study (Figures 4C; Figure 5). 8 Digital dental models were imported into the Stratovan Checkpoint software. Fourteen landmarks were placed on both T1 and T2 dental models (Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…21 To provide a visual representation of the treatment changes in the dental arch shape, an evaluation based on the centroid size and location was performed. 14,30,31 Slight changes were noticed for the secondary outcomes in both groups without intergroup differences (Table 2). The arch perimeter decrease in both groups might have been attributed to natural changes in the late mixed dentition, such as mesial movement of the maxillary molars into the Leeway space.…”
Section: Discussionmentioning
confidence: 93%
“…A total of 14 landmarks on the occlusal surface of the maxillary teeth were used to access arch measurements on the T1 and T2 digital dental models (Figure 1D). 14,15 Maxillary incisor leveling and mesiodistal angulation were assessed using 3DSlicer software (www.slicer.org) (Figure 2).…”
Section: Evaluationsmentioning
confidence: 99%
“…les méta-analyses, les essais contrôlés randomisés et non randomisés, les études cas témoins et les études prospectives et rétrospectives.les études dont le traitement du déficit transversal ScienceDirect : 384 publications et EBSCOhost :424 publications. Après avoir exclu 9 articles répétés, tous les titres et les résumés ont été lus et ceux ne répondant pas aux critères d'inclusion ont été éliminés, 12 articles ont été présélectionnés, dont huit(8) avec disponibilité du texte intégral ont été retenus pour la présente revue systématique. Le processus de sélection est illustré dans le diagramme de Flux(Fig.1)…”
unclassified